Simulation and Comparison of Control Methods of Doubly Fed Induction Generator in Energy Conversion System - Rahmani, Omid; Amiri, Parviz; Mokhtari, Zahra; Amirjamshidi, Zhale (Ciência e Natura, 2015)
One of the most applicable methods for utilization of wind energy is the use of doubly fed induction generator (DFIG). This paper presents two various strategies for control of DFIG in wind energy conversion system. Two most common and best control methods are implemented vector control and direct torque control. The studied control methods and their performance have been compared and analyzed based on the results of stimulation. The results indicate the fact that although direct torque control method is a bit slow at the start time; due to less usage of machine parameters, less complexity of control algorithm and improvement of transient response speed of the system, this method presents better performance compared to vector control method.